Analysis of Pressure Laboratory Scale Swing Adsorption (PSA) Varian Design using Zeolite 13X as Adsorben Medium - Dhimas Satria; Teguh Kurniawan; Rina Lusiani; Erny Listijorini; Imron Rosyadi; Nidya Jullanar Salman (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
The demand of high quality of oxygen increases, especially in the middle of covid -19 pandemic. The importance recentl is using technology and material to improve the quality of oxygen. Therefore a study was conducted which aim to obtain the best varian on concept desain concept analysis of pressure swing adsorption (PSA) which utilize adsorption material of sintetic zeolite 13x. the method used is Quality Function Deployment (QFD) which is information collecting about the need and the willingness of users. The steps carried out to obtain the best variant design concept of pressure swing adsorption are as follow: requirement list determination, priority scale determination, house of quality making, PSA specification determination, design concept and the best variant determination. The result obtained is the selected the best variant which was 10th variant because it has been fulfilled the requirement the specification list because this variant when PSA was used is bed or column type is single bed with the capacity of zeolite of 13X 2 – 2,5 kg, the valve mechanism is manual so that it need no automatic control system, the electricity source was from PLN and need no accumulator and the product of )2 using 1 single tank which is simpler.